A patient with Eradheim-Chester disease presenting with progressive cystic lung lesions and confirmed pulmonary artery hypertension: a case report - Yuxi Wei; Huanwen Wu; Junwei Guo; Xuefeng Sun (BMC Pulmonary Medicine)
Abstract Background Erdheim-Chester disease (ECD), a rare type of non-Langerhans cell histiocytosis, was classified as a haematopoietic tumour by the World Health Organization (WHO) in 2016. It involves multiple systems and is challenging to diagnose due to its broad spectrum of clinical manifestations. The pulmonary manifestations of ECD lack specificity. We present a case of ECD with pronounced cystic lung abnormalities to increase awareness of the disease among pulmonologists and expedite diagnosis and treatment. Case presentation We report the case of a 44-year-old male who presented with intermittent fever, cough, bilateral leg pain, extensive xanthomas on his face, and extensive pulmonary cystic changes noted on imaging following a pulmonary stab wound incident. Thoracoabdominal enhanced computed tomography (CT) revealed progressive cystic changes in the lungs, notably in the upper lungs and subpleural areas; thickened interlobular septa; circumferential wall thickening of the left subclavian artery; uneven thickening of the aortic wall; and soft tissue shadows in the right atrium of the heart. Bone scintigraphy revealed bilateral symmetric long-bone uptake. Despite his advanced lung abnormalities, he exhibited no hypoxia. Notably, echocardiography indicated severe pulmonary artery hypertension, and right heart catheterization confirmed increased mean pulmonary artery pressure at 37 mmHg and elevated pulmonary vascular resistance. Pathology examination of transbronchial lung biopsy and the facial xanthomas confirmed the presence of ECD-characteristic histiocytes, and genetic testing revealed a BRAF V600E mutation. Treatment with dabrafenib improved respiratory symptoms and facial xanthomas, although some symptoms persisted. Follow-up CT showed reduced interstitial lesions but more pronounced cystic changes. Conclusions This case of ECD illustrates rare pulmonary cystic changes alongside pulmonary arterial hypertension, challenging typical presentations of ECD. This is the first documented instance of pulmonary hypertension associated with ECD, broadening the understanding of its potential complications. These findings emphasize the need for considering ECD in the differential diagnosis of atypical cystic lung lesions, especially when accompanied by systemic symptoms such as xanthomas and bone pain.